Lagu Nasional: Sarana Retorika Ideologi Kebangsaan - Yulius Rizki Hutagaol; Ziko Rizky Prabowo; Muhammad Rafli Pradanto; Ovan Bagus Jatmika (Journal of Music Science, Technology, and Industry, 2021)
Purpose: The study aims to discuss the role of the lyric (verbal) and music (non-verbal) aspects in the national anthem as a means of rhetoric for the national ideology (in this case the ideology of the Indonesian nation). Research methods: The method used is qualitative which is more specifically under the umbrella of phenomenological research. Results and discussion: The author chooses the song "Maju Tak Gentar" by C. Simanjuntak. From a semiological point of view, it is known that lyrics are at the first level of significance (denotative) and music is at the second level of significance (connotative). Because the lyrics can be directly identified as the rhetoric of the national ideology, the writer needs to do a further analysis of the music in the national anthem. This can be achieved by linking the characteristics of myth in theory by Roland Barthes to the musical aspects of the song "Maju Tak Gentar". Implication: Music in the national anthem is a form of non-verbal narrative that can be used as a means of rhetoric for national ideology.